Explaining sex differences in existential isolation research. (1st November 2018) - Helm, Peter J.; Rothschild, Lyla G.; Greenberg, Jeff; Croft, Alyssa
Abstract: Existential isolation (EI) is the subjective experience of feeling fundamentally separate from other human beings. Recent studies examining EI have observed a consistent sex difference wherein men report higher levels of EI than women. Our first study used a large undergraduate survey. It replicated the sex difference in EI and showed that controlling for loneliness and self-esteem did not account for this difference. Study 2 replicated this pattern using an online sample, and tested the hypothesis that this difference may be mediated by the sex difference in endorsement of communal and agentic values. We found that sex differences in endorsement of communal (but not agentic) values mediated the sex difference in EI. However, agentic value endorsement played no role. These findings indicate that men may be higher in existential isolation because they do not endorse communal values as much as women do. This suggests that one way to reduce the disproportionate experience of EI among men may be to increase their endorsement of communal values.